IKLAN YANG ETIS DALAM BISNIS MENURUT GEREJA KATOLIK - Jena, Yeremias (Jurnal Teologi (Journal of Theology), 2012)
Advertisement is used effectively as a medium of marketing goods and services. In contrast to the initial appearance where the ad was almost brought a single character, namely to inform the availability of necessary good and services needed, advertising nowadays prefer to create new needs. Its finality was eventually reduced to advertising as a means of expanding the market through the creation of new needs to the point of infinity. Through the power of teaching, the Catholic Church reminds us to create ads that ethically responsible for educating the consumers to the rationality and freedom to buy the good and services. In these two aspects-designing ethical ads and obligation to teach people to be rational-that stands the urgency of this paper.